Feasibility study of 68Ga-labeled CAR T cells for in vivo tracking using micro-positron emission tomography imaging - Wang Xin-yu; Wang Yan; Wu Qiong; Liu Jing-jing; Liu Yu; Pan Dong-hui; Qi Wei; Wang Li-zhen; Yan Jun-jie; Xu Yu-ping; Wang Guang-ji; Miao Li-yan; et al. (Acta Pharmacologica Sinica, 2021)
Clinical tracking of chimeric antigen receptor (CAR) T cells in vivo by positron emission tomography (PET) imaging is an area of intense interest. But the long-lived positron emitter-labeled CAR T cells stay in the liver and spleen for days or even weeks. Thus, the excessive absorbed effective dose becomes a major biosafety issue leading it difficult for clinical translation. In this study we used 68Ga, a commercially available short-lived positron emitter, to label CAR T cells for noninvasive cell tracking in vivo. CAR T cells could be tracked in vivo by 68Ga-PET imaging for at least 6 h. We showed a significant correlation between the distribution of 89Zr and 68Ga-labeled CAR T cells in the same tissues (lungs, liver, and spleen). The distribution and homing behavior of CAR T cells at the early period is highly correlated with the long-term fate of CAR T cells in vivo. And the effective absorbed dose of 68Ga-labeled CAR T cells is only one twenty-fourth of 89Zr-labeled CAR T cells, which was safe for clinical translation. We conclude the feasibility of 68Ga instead of 89Zr directly labeling CAR T cells for noninvasive tracking of the cells in vivo at an early stage based on PET imaging. This method provides a potential solution to the emerging need for safe and practical PET tracer for cell tracking clinically.